Management of Post-LASiK Keratoectasia with a Piggyback Contact Lens System - Haines, Lacey; Sorbara, Luigina (Canadian Journal of Optometry, 2015)
This case report highlights the clinical challenges involved in managing a patient with post-LASiK keratoectasia. A single case is presented with a focus on contact lens fitting and concurrent ocular surface disease. A review of the literature indicates that current screening methods prior to refractive surgery have made improvements for detecting patients at higher risk of serious complications. Possible treatment options for iatrogenic keratoconus include contact lenses, intrastromal corneal ring segments, corneal cross linking, and keratoplasty. This report demonstrates that post-LASiK keratoectasia with concurrent ocular surface disease can be successfully managed with a piggyback contact lens system.